Global Secularisms in a Post-Secular Age - Rectenwald, Michael; Almeida, Rochelle; Levine, George Lewis (Religion and its others, 2015)
Global Secularisms addresses the state of and prospects for secularism globally. It brings together theoretical discussion and empirical case studies that illustrate the "on-the-ground," actually existing secularisms as they interact with various religious, political, social, and economic contexts. The anthology provides unparalleled theoretical scope and detailed empirical granularity in its treatment of secularism and post-secularism.